AKIBAT HUKUM PENDAFTARAN HAK TANGGUNGAN SECARA ELEKTRONIK TERHADAP KEPASTIAN HUKUM AKTA PEMBERIAN HAK TANGGUNGAN YANG DIBUAT DIHADAPAN PPAT YANG PENDAFTARANNYA MELEWATI JANGKA WAKTU. - Pratomo, Suryo Adhi; Kencanawati, Erny; Ridwan, Refki (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyze the legal consequences of electronic registration of mortgage rights to the legal certainty of mortgage deed made in the presence of the land deed officer (PPAT) whose registration passes the specified period. This study examines the impact of the use of electronic mortgage registration system on the validity, validity, and enforceability of deeds carried out under the supervision of PPAT, by raising the issue of how the legal consequences of the deed of Mortgage made before the land deed officer if the electronic mortgage registration past the term and how the legal certainty of the deed. The method used in this research is a normative juridical approach method, namely the fact and legislation approach. The specification of this research is descriptive analysis, namely by describing a condition or position of legal or nonlegal propositions. In this research, the author used primary data types through interviews and observations in the field supported by secondary data in the form of literature studies. Although there is a delay in the registration of the deed of granting mortgage rights (APHT) and the issuance of a Certificate of mortgage rights (HT), it does not cause the cancellation of APHT, as long as it meets the requirements as an authentic deed, because the HT registration process is considered an administrative activity. With the issuance of HT certificate by the Land Office, the creditor obtains legal certainty and preference rights to the HT object in accordance with the provisions of the law. The electronic signing of the HT certificate guarantees the issuance of the HT-EL certificate on the 7th day after receipt of the complete file and payment of non-tax state revenues, even if it falls on a Sunday or holiday. Although the delay in the registration of HT has no legal consequences, it should be noted that in the grace period before the issuance of the HT-EL certificate, the application for confiscation of collateral by the court can potentially harm the creditor because their preference rights may be lost.